Bespoke supply‐chain resilience: The gap between theory and practice - Cohen, Morris; Cui, Shiliang; Doetsch, Sebastian; Ernst, Ricardo; Huchzermeier, Arnd; Kouvelis, Panos; Lee, Hau; Matsuo, Hirofumi; Tsay, Andy A. (Journal of Operations Management, 2022)
AbstractRecent research has documented that companies are pursuing a variety of strategies to enhance supply‐chain resilience. This paper examines how managers actually think about resilience strategies, and then analyzes the relationship between operations, supply‐chain characteristics, and the implemented strategies. We define a “Triple‐P” framework that matches resilience strategies to supply‐chain archetypes by examining Product, Partnership, and Process complexity based on interviews of senior supply‐chain executives. These interviews revealed two major influencers of resilience strategy, that is, Homogeneity of internal supply‐chain processes and Integration with other actors in their end‐to‐end supply chains. We found that the supply chains have different resilience requirements, have different ways to achieve resilience (which we conceptualize as “bespoke supply‐chain resilience”), and face different obstacles to resilience. This study aims at initiating a dialogue between supply‐chain scholars and practitioners to support more research for developing an effective supply‐chain resilience strategy.